Biomechanical analysis of Taekwondo kicking technique, performance and training effects - Hong, Y.; Kam, L. H.; Chung, L. T. (2000)
The purpose of this study was to investigate the kicking technique of Hong Kong Taekwondo athletes and to develop a well-designed training protocol to improve the performance of Taekwondo athletes in Hong Kong. A pre- and post-test design was employed in this study to examine the effectiveness of a training protocol that was based on the outcome of the pre-test. For each test session, the Taekwondo frontal attack kicking technique, such as sidekick, pushing kick, slap kick and back kick, was investigated. Kicking performance was video filmed and the muscle activities were recorded by an electromyography (EMG) system. Based on the recorded EMG signals and the EMG signals obtained from measuring the maximum voluntary contraction (MVC) before the test trial, the percentage MVC (%MVC) was derived. The kinematics of each kicking movement were obtained by digitising and analysing the recorded video tapes on a motion analysis system. The results showed that there were significant differences in kicking time among different styles of kicking (p<.001) and different heights of kicking (p<.001). However, there was no significant difference in kicking time between different preparation forms. The front turning kick to the waist level with standing preparation form was significantly faster (0.70 ± .098s) than the other styles of kicking. However, the one-step sidekick to the head level with standing preparation form was significantly slower (1.09 ± .119s) than other styles of kicking. The muscle activity during kicking was significantly different among selected muscles (p<.001). The vastus lateralis and tensor fasciae latae showed significantly higher average activity when compared with other selected muscles. The average muscle activity for the tensor fasciae latae and the vastus lateralis was 133.12 ± 77.55%MVC and 250.44 ± 182.28%MVC, respectively. This value for sartorius, rectus femoris and vastus medialis was 42.33 ± 14.98%MVC, 66.84 ± 31.31%MVC and 75.98 ± 41.19%MVC, respectively. Muscle activity of hamstrings can be represented by semitendinosus and biceps femoris. The activity level of these two muscles was 43.53 ± 15.43%MVC and 47.14 ± 28.29%MVC, respectively. The isokinetic training protocol was designed with knee concentric extension/flexion at 240deg/s, 20 repetitions in each set, 5 sets for each session, 3 sessions weekly. The isokinetic concentric knee extension peak torque at 240 deg/s showed significant increase from pre- (108.83 ± 16.95 Nm) to post-test (117.83 ± 18.99 Nm) for the training group. It was concluded that isokinetic training at 240 deg/s angular velocity can increase the muscle peak torque of concentric knee extension at that velocity.